W obliczu postindustrialnej restratyfikacji - Wątroba, Wiesław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
A postindustrial society can be described by three dimensions: an increasing predominance of services as opposed to productive business; the central position of theoretical knowledge and the new intellectual technology, and the rise of new technological elites and the transition from a producer society to an information and knowledge society. There are important changes in the social structure, as consequences of the transition of industrial societies into postindustrial ones: a shift in the kinds of work that people do; the change in the occupational structure; the rise of a professional middle class and the knowledge elites; the increased professionalization of work and a shift towards the bureaucratization of 'think1 work. The postindustrial societies are also characterized by the asymmetry of conditions, which expresses itself in the degrees of predictability. Mobility and its absence designate the new polarization of social conditions. Postindustrialism is also a challenge to the traditional role of intellectuals. One of the significant social functions of the intellectual has been the guardianship of high culture and the protection of high culture from popular one. The consequences of globalization are to mix up local and global culture in a new melting pot of multiculturalism. Since high culture cannot be lo cal culture, this effect of globalization has important consequences for the very possibility of the intellectual as a social role. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (10); 2006; nr 1149, s. 51-63